Reconquérir la qualité de l’eau potable par le développement de l’agriculture biologique et de systèmes alimentaires dédiés - Audrey Vincent; Philippe Fleury (EchoGéo)
Organic farming (OF) is seen as a relevant solution to tackle non-point water pollutions. In this paper, we analyse the initiative carried out by the city of Paris to lead to a place-based development of OF in one of its water catchment area (vallée de la Vanne, Yonne). Paris’ water authorities have set up a local organic action plan. We present the project’s main stages. We show that different policy tools and levels of action have been implemented in order to connect the drinking water issue with others such as economic development and food policies (via green public procurements). A scheme to support OF through payments for environmental services has also been established.